1970
DOI: 10.3329/bja.v7i1.3025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Insulin treated Established Diabetes Mellitus (EDM) on the Volume of Placental Parenchyma and Weight of the Neonate

Abstract: Taking in mind the effects of diabetes mellitus of varying severity on human placenta and their implication on the well being of the fetus, a quantitative study at the macroscopic level was designed. Sixty post caesarean section human placentas were studied of which thirty were from mothers having insulin treated established diabetes mellitus (EDM) considered as EDM group and thirty were from control mother having no diabetes mellitus. The venous plasma glucose level (fasting and two hours after breakfast) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The increased placental weight and volume in diabetic mothers were also stated by various authors [14][15][16][17][18][19]. Mayhew et al [20] demonstrated that the placental weight was due to hyperplasia throughout the gestation that was reflected by higher DNA contents and may be endocrine effect of hyperinsulinaemia.…”
Section: Control (N=48) Range (Mini-maxi) Gdm (N=48) Range (Mini-maximentioning
confidence: 68%
“…The increased placental weight and volume in diabetic mothers were also stated by various authors [14][15][16][17][18][19]. Mayhew et al [20] demonstrated that the placental weight was due to hyperplasia throughout the gestation that was reflected by higher DNA contents and may be endocrine effect of hyperinsulinaemia.…”
Section: Control (N=48) Range (Mini-maxi) Gdm (N=48) Range (Mini-maximentioning
confidence: 68%
“…The results of both these studies are in favor of our findings. 16 , 17 Placental cord length, membrane completeness, placental shape, consistency, cord insertion, cord color and gross pathologies showed non-significant results between the two groups but with more propensities in the insulin treated group. Verma has discussed that on major gross examination of placentae, there were non-significant differences which is just similar to our results.…”
Section: Discussionmentioning
confidence: 91%